A Socio-Cultural Analysis of Users’ Intentions to Use Facemasks in the Post Covid-19 Era in Nigeria - Mojisola Bolarinwa; Paul Adeosun (European Scientific Journal, ESJ, 2024)
This paper investigates individuals’ intention to use facemasks in the post-COVID-19 era using the extended unified theory of acceptance and use of technology. The intention to use the facemask during the COVID-19 pandemic was more compelling through enforcement rather than the individual’s will. In the post-COVID-19 era, the effects of facilitating condition, social influence, price value, performance expectancy, effort expectancy, hedonic motivation, experience and habit on the intention to use the facemask were investigated using the regressions analyses. A total of 417 respondents took part in the selection from government organisations, including higher institutions and public offices in South-West Nigeria and the Federal Capital Territory (Abuja). The result shows that facilitating conditions and hedonic motivation positively influenced the intention to use the facemask, while price value, experience and habit have negative impacts. Findings from this study suggest that facemask manufacturers and distributors must suitably define their products and strategies to suit the value perception of the user and beliefs that trigger social status and hedonic motivations in conjunction with the primary health benefits of the facemasks.